Mobile application development, usability, and security - Mukherjea, Sougata 1965- (Advances in multimedia and interactive technologies (AMIT) book series, 2017)
This book provides a thorough overview on the different facets of mobile technology management and its integration into modern society, highlighting issues related to analytics, cloud computing, and different types of application development